Cost-Effective Nursing Practice: Cost -Awareness and Empowerment - Fisher, Patti (Operating Room Nurses Association of Canada Journal, 1993)
Cost-effective nursing practice is essential to succeed today as resources allocated to health care are declining. Realizing that any change poses a threat to our security, it is imperative that stakeholders be permitted to participate in decision-making processes affecting their work. An honest, open exchange of ideas towards cost-effective practices should be encouraged. Cost-effective behaviours are inﬂuenced significantly by negative attitudes with regard to loss of human resources, increased workload, and potential pay cuts. This article describes innovative strategies which could promote successful cost-effective nursing practice, including working smarter, not working harder. Topics addressed are attitude, awareness and empowerment.